Electrospun hexagonal boron nitride/CNT reinforced nanocomposite fiber mats for cosmic radiation shielding - Ersoy, Serra; Ozcan, Mucahid; Kaya, Cengiz; Kaya, Figen (WILEY, 2024)
A novel methodology is introduced to asses the efficacy of cosmic radiation shielding through the fabrication of electrospun nanocomposite fiber mats reinforced with hexagonal boron nitride (h-BN) and carbon nanotubes (CNTs). These mats were fabricated using various h-BN particles synthesized with 1 M boric acid and four distinct 1 M nitrogen sources to produce polyethylene oxide (PEO) nanofibers via the electrospinning method at 15 kV, a 43.0 mu L/min pumping rate, and a 20 cm distance with a maximum thickness of 10 mu m. High neutron shielding capability nanocomposite fibers denoted BN-F4 (spun with h-BN [melamine]/CNT powders in a 5 wt% PEO solution) and BN-F5 (spun with h-BN [urea]/CNT powders in a 5 wt% PEO solution) were produced. By calculating the theoretical photon transmittance and evaluating the neutron shielding efficiency with an Am-Be neutron source and a BF3 neutron detector, the cosmic radiation shielding capability of nanocomposite mats was discussed. BN-F4 and BN-F5 exhibited neutron shielding properties of 7.124% and 6.37% for 3.82 and 1.87 g/mL, respectively. This research establishes a new benchmark in the fabrication of flexible, ultrathin, and lightweight radiation shielding materials and enhances the practicality of nanocomposites reinforced with h-BN and CNTs by incorporating synthesizing and characterizing steps.
Keywords: boron nitride; carbon nanotubes; electrospinning; nanocomposite; radiation shielding; Chemistry; Materials Science; Polymer Science